Multilocus Sequence Typing of Treponema pallidum subsp. pallidum in Cuba From 2012 to 2017 - Grillová, Linda; Noda, Angel A; Lienhard, Reto; Blanco, Orestes; Rodríguez, Islay; Šmajs, David (The Journal of infectious diseases, 2019)
BACKGROUND: The increased prevalence of syphilis in Cuba prompted us to map the circulating Treponema pallidum subsp. pallidum allelic profiles in this geographic region. METHODS: Samples were collected from 2012 to 2017, from 83 male patients with ulcers or skin lesions, and were examined using multilocus sequence typing. Additionally, we analyzed the 23S rDNA and 16S rDNA regions for the presence of possible mutations leading to macrolide and tetracycline resistance. RESULTS: Among 94% of fully typed strains, we found 7 different allelic profiles, of which 4 had not been previously described. More than 87% of patients were infected with the T. pallidum SS14-like group and only 8.2% with T. pallidum Nichols-like group. As in other countries, the 1.3.1 allelic profile (ie, SS14-like) was the most common. In addition, 1 of the newly described allelic profiles represents T. pallidum strains that arose by recombination events between members of different T. pallidum subgroups. More than 90% of patients were infected with treponemes harboring the A2058G mutation. However, we found no potential tetracycline-resistant T. pallidum mutations. CONCLUSIONS: Our results suggest that, in Cuba, tetracycline antibiotics could be used to treat syphilis in penicillin-allergic patients instead of macrolides.
Keywords: alely; Macrolides; Humans; syfilis; techniky typizace bakterií; Multilocus Sequence Typing; mutace; Tetracycline; dospělí; Alleles; lidé; antibakteriální látky; Adult; Anti-Bacterial Agents; Male; Drug Resistance, Bacterial; multilokusová sekvenční typizace; Cuba; Kuba; tetracyklin; Syphilis; Bacterial Typing Techniques; bakteriální léková rezistence; Treponema pallidum; Mutation; mužské pohlaví; makrolidy